(untitled) (Journal of history, 2018)
The languages of the Turkic peoples left many traces in a variety of languages. Turkism – any word in the language of the Turkic languages included in the entrance. The relationship between the Republic of Kazakhstan and Poland began in the XIX century. Polish language and Turkic languages are not related languages. The Polish language includes the roots of the words of Turkic origin. The purpose of the article is to reveal the factors of penetration of the Turkism into the Polish language and to make comparative-comparative analysis of Turkic words.